Association of Coronavirus Infection with Higher Mortality Rate and Longer Hospital Stay in Patients with Major Extremity Fractures - Chawla, Ashwin; Angthong, Chayanin; Ratta-Apha, Khanatchet (My University, 2025)
BACKGROUND: The Coronavirus disease 2019 (COVID-19) pandemic has significantly affected healthcare systems, raising concerns about patient outcomes, particularly for those with coexisting conditions. Despite various studies on orthopedic injuries during the COVID-19 pandemic, differences in treatment outcomes remain insufficiently known. This retrospective cohort study investigated the effects of SARS-CoV-2 infection on patients with major extremity fractures requiring surgery. We hypothesized that patients with COVID-19 would experience longer hospital stays (LOS) and higher mortality rates. MATERIAL AND METHODS: Data from 500 patients (mean age 47.1 years; 69.8% male) admitted to our hospital between March 2020 and July 2022 were analyzed. We collected demographic data, COVID-19 test results, fracture-related data, LOS, and mortality-related data. RESULTS: Of the patients, 23 (4.6%) had COVID-19. While overall LOS showed no significant prolongation in patients with COVID-19, a significantly longer LOS was observed for patients with COVID-19 and lower extremity fractures (14.62 vs. 11.39 days, p<0.00001) and upper extremity fractures (11.90 vs. 5.73 days, p=0.0271). CONCLUSIONS: 1. Patients with COVID-19 exhibited a markedly longer LOS than those without COVID-19, with this effect being more pronounced in patients with lower extremity fractures. 2. When all patients had major extremity fractures, patients with COVID-19 had a significantly higher mortality rate than those with out COVID-19.
Keywords: COVID-19; epidemiology; extremity; fractures; SARS-CoV 2